PERANCANGAN SISTEM INFORMASI GEOGRAFIS MENGGUNAKAN PETA DIGITAL - Deny Wiria Nugraha (Foristek, 2012)
In electrical engineering technology, especially information technology today can be applied to all areas of life. In this rapid technological developments, information technology can be utilized as a means of information for the primary electrical distribution channels in the form of a geographic information system making it easier for users of the system to determine thecondition of the electrical distribution channel. This study uses a program that comes with ArcView Avenue script programming to implement a geographic information system primary electrical distribution channels in the city of Palu using digital maps. Geographic information system designedand fabricated in this study proved capable of displaying all the information on the primary electrical distributionchannels in which the data taken from the PT. PLN (Persero) rayon branch of Palu city.